Estimation of C-reactive protein (CRP), serum uric acid (UA) and LDH in women with preeclampsia - Renu; Balwinder Kaur; Ashok Kumar; Beant Singh; Maninder Kaur; Manjeet Kaur Mohi (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: For pre-eclampsia with the involvement of various systems, several markers have been proposed. The value of CRP indicates the severity of endothelial cell injury. Endothelial cell injury is one of the responsible factors for developing or initiating preeclampsia. During pre-eclampsia due to the extent of cellular death, the severity of the disease can be assessed by serum LDH levels. Serum uric acid levels reflect the circulating xanthine oxidase activity and oxidative stress production. Objectives: The objective of this study was to find out the correlation of C-reactive protein, serum uric acid and serum LDH with the severity of pre-eclampsia. Methodology: Serum levels of CRP, LDH and uric acid were estimated among the study group included of preeclamptic & eclamptic antenatal patients (n=150) and the control group included normotensive antenatal women (n=50). Student t-tests and chi-square tests were used for statistical analysis. Results: The mean value of CRP in the study group was 24.80 ±24.70 mg/L which was significantly higher than the control group i.e. 1.20± 4.37 mg/L (p =0.001). The mean value of serum uric acid level in the study group was significantly higher (6.16±3.39 mg/dl) than in the control group (3.09±0.53 mg/dl) (p= 0.001). The mean value of LDH in the study group was also significantly higher 698.95±624.08 U/L than 301.24±124.59 U/L in the control group (p= 0.001). Conclusion: Monitoring of CRP, LDH and uric acid can help diagnose the severity, and progression of the disease process and help prevent maternal complications. Increased serum CRP level is correlated with preeclampsia being an indirect risk factor for placental vasculopathy predating clinical preeclampsia.